PREPARATION AND CHARACTERIZATION OF SOLID DISPERSION LOADED WITH SELEXIPAG AS MODEL DRUG - KARAM, DOAA HUSSEIN; ABDUL-HASAN, MAZIN THAMIR (International Journal of Applied Pharmaceutics, 2026)
Objective: The study aims to prepare solid dispersions of selexipag to enhance its aqueous solubility using two different techniques—solvent evaporation and kneading. Methods: Twenty-seven solid dispersion (SD) formulations of selexipag were prepared using two different techniques, solvent evaporation (SE) and kneading (KN). Various hydrophilic carriers were employed, including urea, polyethylene glycol 4000 (PEG 4000), polyethylene glycol 6000 (PEG 6000), poloxamer 188 (PXM 188), and poloxamer 407 (PXM 407), at drug-to-polymer ratios of 1:1, 1:3, and 1:5. The prepared formulations were evaluated for saturation solubility, drug content, percentage yield, and in vitro dissolution. Fourier transform infrared spectroscopy (FTIR) was performed to assess drug-polymer compatibility. Results: The saturation solubility was enhanced by all prepared solid dispersion formulations. The pure selexipag exhibited a solubility of 1.5±0.04 µg/ml, whereas the optimized formulation (F2, PXM407:Selexipag 3:1) prepared by the solvent evaporation method showed a solubility of 25.9±0.2 µg/ml, representing approximately a 17-fold increase compared to the pure drug. The optimized formulation also demonstrated a faster dissolution rate, with 88% of the drug released within 30 min. FTIR results further confirmed drug-carrier compatibility; no additional peaks were observed in any of the binary systems, indicating the absence of chemical interaction between selexipag and the polymer. Conclusion: Solid dispersion, particularly using poloxamer 407 via solvent evaporation, proved to be an effective and promising approach for enhancing the solubility, dissolution rate, and overall biopharmaceutical performance of selexipag.